1993
DOI: 10.1002/pola.1993.080310117
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and thermal properties of aryl‐substituted rod‐like polyimides

Abstract: This article describes the synthesis and thermal characterization of novel aryl‐substituted rod‐like homopolyimides. Synthetic aspects of monomer syntheses and one‐step polymer synthesis in m‐cresol are presented. Polyimides with rod‐like chain structure are based on monophenylated pyromellitic dianhydride (MPPMDA), diphenylated pyromellitic dianhydride (DPPMDA), and as rod‐like diamine units on phenylated para‐phenylene diamine and 1,1′‐binaphthyl‐4,4′‐diamine. As partial flexible units, which have the possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
52
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 30 publications
0
52
0
Order By: Relevance
“…Several attempts have been made to improve the solubility of polyimides while maintaining the excellent thermal and mechanical properties. 1 - 9 One attractive method to improve solubility is the introduction of bulky pendant phenyl group into the polyimide backbone, and a number of organic soluble polyimides having high Tgs have been successfully prepared by using aromatic diamines containing tetraphenylthiophene, 1 0 · 11 tetraphenylfuran, 12 tetraphenylpyrrole, 13 triphenylamine, 14 triphenylbenzene, 15 and tetraphenylquinquephenyl. 16 Recently, we synthesized organic soluble polyamides having high thermal stability from 1,4-bis-(4-aminophenyl)-2,3-diphenylnaphthalene and various aromatic acid dicarboxylic acid chlorides.…”
mentioning
confidence: 99%
“…Several attempts have been made to improve the solubility of polyimides while maintaining the excellent thermal and mechanical properties. 1 - 9 One attractive method to improve solubility is the introduction of bulky pendant phenyl group into the polyimide backbone, and a number of organic soluble polyimides having high Tgs have been successfully prepared by using aromatic diamines containing tetraphenylthiophene, 1 0 · 11 tetraphenylfuran, 12 tetraphenylpyrrole, 13 triphenylamine, 14 triphenylbenzene, 15 and tetraphenylquinquephenyl. 16 Recently, we synthesized organic soluble polyamides having high thermal stability from 1,4-bis-(4-aminophenyl)-2,3-diphenylnaphthalene and various aromatic acid dicarboxylic acid chlorides.…”
mentioning
confidence: 99%
“…28 Interestingly, the polyimide from BPDA and 2,5-diaminobiphenyl, an isomer of 3,3Ј-DABP with para-oriented substitution, has a T g of 341°C, 29 so that, the T g decrease must be attributed again to the conformational freedom imposed by the 3,3Ј-DABP diamine to the macromolecular chain.…”
Section: Polymers Syntheses and Propertiesmentioning
confidence: 97%
“…It has been reported that polyimides based on phenyl-substituted pyromellitic dianhydride (PMDA) have much better solubility than rigid poly(aryl pyromellitimide)s. 11,12 We further described a series of soluble high-T g polyimides derived from a dianhydride structurally analogous to phenylated PMDA. 13 It was found that the pendant phenyl groups can impart solubility to the polyimides without sacrificing their thermal stability.…”
Section: Introductionmentioning
confidence: 99%